Comparative assessment of beef, chevon and mutton biltong cured with ocimum gratissimum paste (2017)
Meat not processed after slaughter deteriorates, hence processing is needed to hinder microbial growth for longer shelf life in biltong. The study was carried out to comparatively assess responses of biltong from different meat types (beef, chevon and mutton) to Ocimum gratissimum paste (Ogp) as curing agent. The paste was obtained by blending the leaves of basil into paste (1.360 kg). Meat chunk of beef, chevon and mutton were stripped into approximately 8 - 10 x 2 x 1.5 cm along the grains. There were six treatments and each replicated twenty times. In a Completely Randomized Design using factorial arrangement treatments were tagged. T1, T3, T5 for controls (no Ogp) while T2, T4, T6 were treatments of beef, chevon and mutton respectively cured in (Ogp) paste for a period of 10 hours and mildly seasoned. After curing, meat strips were dipped into a mixture of hot water (100°C) and vinegar for two hours to prevent mould growth. The strips were then sundried (from 7a.m-6p.m) under insect proven condition, they were thereafter left to dry at room temperature for two weeks (at 27°C and 75% relative humidity). The proximate, minerals, organoleptic properties, microbial counts and characterisation of biltong were investigated. It was observed that the highest preference was given to beef biltong (T2) and chevon biltong (T2) in terms of overall acceptability while mutton biltong was least preferred. The aerobic bacteria, coliform and lactic acid counts were more in uncured biltong meat types while the cured mutton biltong (T6) had the least bacterial and lactic acid counts however, the highest counts was recorded in beef biltong (T2).